OPTIMALISASI WAKTU DAN BIAYA PROYEK DENGAN METODE CPM DAN PERT DI PROYEK ABC CONDOTEL - Putri Endah Suwarni (Fakultas Teknik Universitas Tulang Bawang Lampung, 2019)
Planning until controlling process during construction work are important activity of a project. Success or failing of the project caused by not maximal planning and insufficiently effective controlling, so that the project activity is inefficient. As the consequences of these impacts suffered project delay, decreasing of quality, and increasing performing cost. Project management working time drew the line by given schedule, so the manager of project shall get to anticipate condition changing. CPM and PERT methods can be used to manage the time of project completion more efficiently and effectively. To be able to reduce the impact of delays and swelling of project costs, a crashing process can be proposed with additional working hours. Duration acceleration is carried out on the work that is on the critical path because the work on the critical path does not have a delay time. With the addition of working hours besides being able to shorten the completion time, it also results in additional operational costs. Keywords : Project management, CPM and PERT method.